Highly defective NiFeV layered triple hydroxide with enhanced electrocatalytic activity and stability for oxygen evolution reaction - Li, Xi-Yuan; Xu, Lin-Cheng; Wang, Yue; Yan, Yong; Feng, Ying-Jie; Li, Fan (Frontiers in Materials, 2024)
Oxygen evolution reaction (OER) is one of the most important components of various electrochemical systems such as water splitting, metal air batteries, and carbon dioxide reduction. However, the four-electron process of OER suffers from intrinsically sluggish kinetics, which contributes to significant overpotential in the electrochemical system. Herein, highly defective NiFeV layered triple hydroxide (LTH) catalysts was efficiently prepared using a one-step hydrothermal method. The crystal structure, electronic structure, and surface composition of NiFeV LTH were characterized by X-ray diffraction and photoelectron spectroscopy. Moreover, NiFeV LTH demonstrated a superior OER catalytic performance with-low overpotential (158 mV @10 mA•cm -2 ), related small Tafel slope (102.3 mV•dec -1 ), and long-term stability at a high current density of 100 mA•cm -2 . In situ Raman spectroscopy was applied to investigate the surface reconstruction during the OER process. It is revealed that Ni species were the most active sites at low overpotential, with the potential increasing subsequently Fe and V gradually participates in the catalytic reaction, the Fe and Ni species as OER catalytic active sites lead to the excellent OER catalytic activity of NiFeV LTH, and inhibited the further dissolution of high-valence NiOOH at high overpotential. The mechanism induced the outstanding activity and stability at high current densities in NiFeV LTH system. Dissolution of vanadium excited the active sites of NiFeV LTH synthesized by hydrothermal method which promoted both activity and stability, while the changes of surface species at different OER potentials were detected by in situ Raman spectroscopy.